Microstructure study of Ce-doped – Ceramics containing Zinc and Cerium oxides - Ibrahim, D. E.; Desouky, Osama (Al-Mukhtar Journal of Sciences, 2004)
Ceramics are finding increasing application in the world of electronics. These application range from surge arrestors (varistors) to postive temperature resistors to ceramic dielectrics and their application in microwave componets to magnetics ferrites to pyroelectric devices etc. The microstructure of Ce-doped ZnO cermics , revealed the presence of a liquid phase between cermic and ZnO .An inter-granular phase rich in ceium is made from this liquid , occurs at grain corners . The addition of 0.25 mol% of each Co and Cr2O3 and / or 0.5 mol% Bi2O3 participated and inceased the formation of this liquid phase as indicated by EDAX . Cerium was detected partly with in the ZnO grains and mainly in this intergraular phase togather with ZnO alone and Cr2O3 and or Bi2O3 .The liquid phase enhanced the preferential grain growth of the ZnO grains.